Zakat for Mama Biang in Maluku, Indonesia: Ulama Opinion on Fīsabīlillāh in the Perspective of Islamic Legal Anthropology - Hannani, Hannani; Haq, Islamul; Amiruddin, Muhammad Majdy; Haramain, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Giving zakat to mama biang is one of the problems of zakat distribution that has attracted controversy. In the people of Negeri Iha, Maluku, the giving of zakat mama biang has become a tradition that has survived into the modern era. The purpose of this study is to study the practice of distributing zakat to Mama Biang, the opinions of tafsir scholars and the implications for Islamic law. The study uses empirical legal studies with an anthropological approach to Islamic law. While data collection techniques are in-depth interviews and literature studies. This study concluded that the controversy over the distribution of zakat mama biang occurred due to differences in scholars' interpretations of the meaning of fīsabīlillāh which had implications for differences in people's understanding of Islamic law. People who maintain the tradition of zakat mama biang understand that the distribution of zakat mama biang is in accordance with Islamic law, relying on the opinion of scholars who expand the meaning of fīsabīlillāh to include mama biang. Meanwhile, some people understand that mama biang zakat is not in accordance with Islamic law. The controversy over the distribution of zakat to mama biang also occurs because zakat is not distributed evenly to all existing asnaf, this can also trigger gaps in society. Therefore, in the perspective of legal anthropology, the practice of giving to mama biang can continue as a local tradition, but this gift can be categorized as infaq or sadaqah, not zakat. So that this can give birth to harmonious legal implications between Islamic law and adat which has become living law.